Training in the care of the common home: sustainable tourism as a driver for an integral ecology - Patrizia Galeri (Firenze University Press, 2021)
The growing importance that the sustainability is experiencing, in relation to the territorial culture, highlights the need to educate people who will be able not only to guide territorial initiatives and resources, but also to create synergies among different subjects, increasing as a consequence the relational capital and diversifying sustainable touristic projects in order to respond to the characteristics of a fare development. Sustainable tourism and the education that lies at its basis are related to the interpretation of green economy current heuristic curves and outcomes, which offers the possibility of creating jobs and boosting innovative activities. Sustainable tourism, whose main features are here described and compared to other types of tourism, is strictly related to the topics and the issues concerning human development, being nowadays a powerful driver to increase placement.   Formazione alla cura della casa comune: il turismo sostenibile come driver per un'ecologia integrale L'importanza sempre maggiore assunta dalla sostenibilità in riferimento alla cultura del territorio, evidenzia la necessità di formare persone capaci di orientare le iniziative e le risorse territoriali, di creare sinergie tra i molti soggetti, producendo un incremento del capitale relazionale e una diversificazione di progetti turistici sostenibili per rispondere alle esigenze di sviluppo equo e solidale. La prospettiva del turismo sostenibile e della sua formazione è connessa con un'interpretazione delle attuali curvature e risultanze euristiche della green economy, che offre possibilità per la creazione di lavoro, e di attività creativo-innovative. Il turismo sostenibile, di cui si offre una disamina dei contenuti e dei valori in parallelo ad altre forme di turismo, è in profonda sintonia con i temi e le prospettive dello sviluppo umano e rappresenta, oggi, uno straordinario driver per potenziare il placement.